Genomic Characterization of Salmonella Typhimurium Isolated from Guinea Pigs with Salmonellosis in Lima, Peru - Dennis E. Carhuaricra Huaman; Luis R. Luna Espinoza; Carmen L. Rodríguez Cueva; Carla G. Duran Gonzales; Raúl H. Rosadio Alcántara; João C. Setubal; Lenin Maturrano Hernández (Microorganisms, 2022)
Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) is one of the most important foodborne pathogens that infect humans globally. The gastrointestinal tracts of animals like pigs, poultry or cattle are the main reservoirs of Salmonella serotypes. Guinea pig meat is an important protein source for Andean countries, but this animal is commonly infected by S. Typhimurium, producing high mortality rates and generating economic losses. Despite its impact on human health, food security, and economy, there is no genomic information about the S. Typhimurium responsible for the guinea pig infections in Peru. Here, we sequence and characterize 11 S. Typhimurium genomes isolated from guinea pigs from four farms in Lima-Peru. We were able to identify two genetic clusters (HC100_9460 and HC100_9757) distinguishable at the H100 level of the Hierarchical Clustering of Core Genome Multi-Locus Sequence Typing (HierCC-cgMLST) scheme with an average of 608 SNPs of distance. All sequences belonged to sequence type 19 (ST19) and HC100_9460 isolates were typed in silico as monophasic variants (1,4,[5],12:i:-) lacking the fljA and fljB genes. Phylogenomic analysis showed that human isolates from Peru were located within the same genetic clusters as guinea pig isolates, suggesting that these lineages can infect both hosts. We identified a genetic antimicrobial resistance cassette carrying the ant(3)-Ia, dfrA15, qacE, and sul1 genes associated with transposons TnAs3 and IS21 within an IncI1 plasmid in one guinea pig isolate, while antimicrobial resistance genes (ARGs) for β-lactam (blaCTX-M-65) and colistin (mcr-1) resistance were detected in Peruvian human-derived isolates. The presence of a virulence plasmid highly similar to the pSLT plasmid (LT2 reference strain) containing the spvRABCD operon was found in all guinea pig isolates. Finally, seven phage sequences (STGP_Φ1 to STGP_Φ7) were identified in guinea pig isolates, distributed according to the genetic lineage (H50 clusters level) and forming part of the specific gene content of each cluster. This study presents, for the first time, the genomic characteristics of S. Typhimurium isolated from guinea pigs in South America, showing particular diversity and genetic elements (plasmids and prophages) that require special attention and also broader studies in different periods of time and locations to determine their impact on human health.